ANALYSIS IMPLEMETATION OF COOPERATIVE LEARNING IN ENGLISH CLUB FOR INFORMATICS ENGGINEERING STUDENTS PAMULANG UNIVERSITY - Darmawati Darmawati; Sulasih Sulasih (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
This qualitative research aims to explore the implementation of cooperative learning in English club activities for Informatics Engineering students at Pamulang University. The study focuses on investigating the effect of cooperative learning on students' English language skills, as well as identifying the benefits and obstacles of using cooperative learning approach in the context of English club activities. The research used a case study design, where data were collected through observation, interviews, and document analysis. The participants were selected purposively from the members of the English club, and the data were analyzed using a thematic analysis approach. The findings suggest that cooperative learning has a positive impact on students' English language skills, particularly in terms of improving their speaking and listening abilities. Moreover, the study identifies several benefits of using cooperative learning, such as increased motivation, enhanced collaboration, and greater engagement. However, the study also reveals some challenges associated with the implementation of cooperative learning, including the need for sufficient planning and organization, as well as the issue of student participation. These findings have significant implications for the development of effective cooperative learning strategies in English club activities for Informatics Engineering students at Pamulang University.